Synthesis and Characterization of Syndiotactic Polystyrene-Polyethylene Block Copolymer - Lamparelli, David Hermann (Polymers (Basel), 2019)
The direct synthesis of syndiotactic polystyrene-block-polyethylene copolymer (sPS-b-PE) with a diblock structure has been achieved. The synthetic strategy consists of the sequential stereocontrolled polymerization of styrene and ethylene in the presence of a single catalytic system: cyclopentadienyltitanium(IV) trichloride activated by modified methylaluminoxane (CpTiCl(3)/MMAO). The reaction conditions suitable for affording the partially living polymerization of these monomers were identified, and the resulting copolymer, purified from contaminant homopolymers, was fully characterized. Gel permeation chromatography coupled with two-dimensional NMR spectroscopy COSY, HSQC, and DOSY confirmed the block nature of the obtained polymer, whose thermal behaviour and thin film morphology were also investigated by differential scanning calorimetry, powder wide angle x-ray diffraction, and atomic force microscopy.